Chemoprotective effect of melatonin against cisplatin-induced testicular toxicity in rats - Ateşşahin, A; Şahna, E; Türk, G; Çeribaşı, Ao; Yılmaz, S; Yüce, A; Bulmuş, Ö (My University, 2006)
In this study, we investigated the effect of melatonin on cisplatininduced spermiotoxicity using quantitative, biochemical and histopathological approaches. Cisplatin (CP, 7 mg/kg) and melatonin (10 mg/kg) were intraperitoneally injected. The rats were decapitated on 5th (short-term group) or 50th day (long-term group) after CP injection. Traits of reproductive organs, sperm characteristics, testicular histological findings, and the lipid peroxidation in the testicular tissue were determined. Melatonin mitigated CP-induced reductions in testes, epididymis and accessory gland weights in rats decapitated on day 5. Both short- and long-term CP treatment decreased sperm concentration, sperm motility and increased abnormal sperm rates compared with the control. But the reduction of sperm concentration in long-term CP treatment was insignificant. Although treatment with melatonin provided moderately normalization with respect to sperm concentration in short-term treatment group, melatonin caused a marked normalization of sperm motility in both CP + melatonin groups. Both groups treated with the melatonin showed decreases in abnormal sperm rates compared with alone CP. While testicular malondialdehyde levels were elevated after CP treatment, glutathione peroxidase activity decreased significantly in both groups. Glutathione levels reduced after long-term treatment, but not in short-term group by CP administration. Treatment with CP plus melatonin provided significant amelioration of oxidative stress parameters. Histopathological findings of testes in both short- and long-term treatment groups paralleled the biochemical and spermatogenic results. This study clearly indicates that CP-treatment impaired markedly testicular function and combined treatment with melatonin prevented much of the toxicity in rats.
Sıçanlarda sispilatinin neden olduğu testiküler toksisiteye karşı melatoninin koruyucu etkisi
Makale - Yabancı Dilde Makale
Keywords: cisplatin histopathology lipid peroxidation melatonin oxidative stress sperm characteristics